An assessment of the Command and General Staff Officer Core Course effectiveness in developing student critical thinking - Civils, Timothy H., Jr (Kansas State University, 2016)
There is a need for critical thinking skills in our society. This research study examines graduate student’s growth in critical thinking after experiencing a specifically designed curriculum. This study evaluated the effectiveness of the U.S. Army Command and General Staff Officer Common Core Course to change student critical thinking skills and habits of the mind attributes, and further examined instructor perceptions of the curriculum, instructional methods, and instructor skills and behaviors that impact student critical thinking development within the Core Course. This study used an explanatory sequential mixed method research design in order to answer the four research questions and test their respective hypotheses. Eight student staff groups (n=120) were selected from the Command and General Staff Officer Common Core Course Class 15 population, and the quantitative data used to conduct the analyses was derived from a pretest and posttest using the Military and Defense Critical Thinking Inventory (MDCTI), a nationally recognized instrument designed specifically for individuals in the defense and military profession. The qualitative component of the study consisted of focus group interviews conducted with instructors from the eight selected staff groups (n=24) to examine their perceptions on the role of the curriculum, instructional methods, and instructor skills and behaviors in developing student critical thinking. The data collected from these interviews were analyzed and presented using a collective case study approach. Analysis of the student pretest and posttest score change results indicated statistically significant changes in analysis, induction, deduction, and overall critical thinking skills, and in the communicative confidence, professional confidence, expression, and directness habits of the mind attributes. Further analysis indicated that there was no statistically significant change differences in critical thinking skills or habits of the mind attributes between the teaching team groups. Analysis of the qualitative data revealed nine themes that were categorized within the theoretical framework of curriculum, instructional methods, and instructor skills and behaviors. Four additional themes emerged which did not address the role of curriculum, instructional methods, and instructor skills and behaviors in developing student critical thinking. These themes included: lack of contact time, the importance of the physical classroom configuration, the military/school culture, and student attributes.
Keywords: Critical thinking; Graduate students; Team teaching; Dispositions; Cohorts; Adult learners